IDENTITY OF CITIZENS OF UKRAINE: PROBLEM OF SELF-DETERMINATION AND ORIENTATIONS - Стогова, О.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The problem of identity of citizens of modern Ukraine is examined in the article. An author analyses a social identity, factors of its forming, civil identity as the constituent of social. A political identity as problem of self-determination is investigated. Drawn conclusion about the necessity of realization of purposeful politics the state on forming of national-state identity that must be based on traditional values and master rationalism of "western" type of identity.